Studi Indeks Kepuasan Masyarakat Terhadap Pelayanan - Kamil Kamil (Jurnal Medika : Karya Ilmiah Kesehatan, 2017)
Background: Patient Satisfaction is the reflection of the health service quality they receive. To find out the service performance of the government officials to the public, it is necessary to assess the public opinions about their satisfaction toward the services provided in the Laboratory. Based on the Decree of Minister of State Apparatus Empowerment Number: Kep/25/M. PAN/2/2004 concerning the General Guidelines for Preparing Public Satisfaction Index in the Government Institution Service Units, it is necessary to do assessment on the satisfaction index toward public services. Then the 14 indicators were used as an assessment instrument based on the decree of Minister of State Apparatus Empowerment. Methods: The sample was taken by using Non Probability Sampling with the total number of 150 respondents taken from the patients who visited the Laboratory of UPTD Puskesmas Wonorejo. The research was conducted in May 2016. The data were analyzed descriptively and the value of Public Satisfaction Index (PSI) was calculated. Findings: The research findings showed that the value of public satisfaction index of PSI was 74.065 in which the service quality was categorized B or good. Conclusion: Public Satisfaction Index toward the services provided by Laboratory at UPTD Puskesmas Wonorejo Samarinda was 74.085 with good service performance .